Classification of the business processes of commercial enterprise on the basis of process approach - Hanna Sytnyk (Cхід, 2013)
Modern approaches on classification of the business processes of enterprise are analyzed in this Paper. On the basis of its generalization and development the additional classification features of its division are formulated, systematisation of the types of business processes of commercial enterprise is made, author's referential model of business processes for commercial enterprises as the basis for the implementation of process oriented financial planning is set forward.